The Application of Problem Posing Learning Model to Improve Physics Learning Outcomes on Sound Wave Material - Maulina, Raiyan; Wahyuni, Agus; Halim, A (Asian Journal of Science Education, 2020)
This study aimed to find out how to apply the problem posing model to improve physics learning outcomes in class XI. This study used a descriptive statistical approach, and it was a gradual study. The stages used in this study were planning, implementing, observing, and reflecting. The subjects in this study were 30 students of class XI IA1 of SMAN 1 Lhoknga. The improvement shown in the average score obtained by students and and the classical limitations from cycle I to cycle III, namely 40%, 54%, 94% and 50%, 70%, 90%. Learning outcomes obtained by students can be improved by: students practice to understand the material conveyed by the teacher and students practice to respond the learning conveyed by the teacher.Keywords: Problem posing, learning, learning outcomes